Request for Blood Components Packed Red Cell at UDD PMI Sukoharjo in Quarter I of 2021 - Anisa Wahyu Wijayanti; Syarifah; Titis Wahyuono (Nur Science Institute, 2023)
Packed Red Cell (PRC) is the most requested at the Blood Donation Unit (BDU) of Indonesia Red Cross (IRC) Sukoharjo Regency. PRC requests are usually transfused to patients of varying sex, ages, and blood types that vary according to need. PRC is widely used in the treatment of anemia, thalassemia, leukemia, aplastic anemia, and the consequences of other malignancies. This study aims to get an overview of PRC demand at BDU of IRC Sukoharjo Regency. This study used a quantitative descriptive design with a cross-sectional approach, the population was 2,693 and the sample was 348 patients at the BDU of IRC Sukoharjo Regency from January to March 2021. Sampling with purposive sampling technique, then the secondary data was analyzed by univariate analysis using Microsoft Excel 2010. The sample of PRC requests was 348 patients. With female gender 184 (53%) patients and male 164 (47%) patients. There is a request for PRC with blood type A positive 93 (27%) patients, B positive 105 (30%) patients, O positive 118 (34%) patients, AB positive 32 (9%) patients. Based on age with a range of <1 year 3 (1%) patients, 1-20 years 76 (22%) patients, 21-40 years 102 (29%) patients, 41-60 years 116 (33%) patients, 61-80 years 49 (14%) patients, and >81 years 2 (1%) patients. There is a majority demand for PRC in female patients, age range 41-60 years, with O positive blood type at BDU of IRC Sukoharjo Regency.